Plan de negocios para la distribución de la gaseosa barrilitos O’key para el canal detallista del cantón Quevedo, año 2014 - Fuentes Garcia, John Alex (2015)
In Quevedo O'Key lacks a distribuidora of gassy Kegs for the channel retailer, specialized in the sale and delivery of the product that satisfy the demand and the necessities of the client’s tradesmen. One has seen the necessity to make this business plan, to satisfy the demand of the market of Quevedo, since it doesn't have a distribuidora expendedora that is devoted to the distribution of the gassy Kegs exclusively O'Key to the channel retailer, there is not any direct company or indirectly that they operate in the market offering the products, hence the main objective is to evaluate the market of Quevedo on a plan of businesses for the distributor of gassy kegs O'Key for the channel retailer and to determine its demand. The present project offers a solution to the tradesmen from the channel retailer to the moment to need or to require our product, visiting and offering our soda and I stack efficient the delivery. This project presents a plan of businesses to start a distribuidora of gassy Kegs O'Key to the channel retailer who took charge efficiently of all the sales and delivery of the product. The strategies to take this project ahead will be the visits and effective delivery of the product, for fidelizar to our clients will use POP material, posters and gifts for our clients. The name of the distribuidora will be JF, which took charge of offering a good service and efficient in the sale and delivery of the product kegs O'Key to the channel retailer of the city of Quevedo, domiciled in the city of Quevedo via valency km 4 1/2. A total investment of USD $ is required 19.304,00. The total of expenditures for the first year is of USD $ 352.812,71 while the total of revenues for the first year is of USD $ 384.000,00 the net utility is of $ 7.329,01 understanding each other as a completely viable project.